Unilateral macular choroidal neovascularization—a rare manifestation in acute myelocytic leukemia: Case report. Issue 16 (April 2018) - Yang, Xiaochun; Xu, Jianbiao; Yang, Jianhui; Zhou, Yikun; Mei, Yan; Yang, Tonghua; Zhang, Yangmo
Abstract: Rationale: Characteristic signs of leukemic retinopathy include bilateral intra-retinal hemorrhage, white-centred hemorrhage, macular hemorrhage and cotton-wool spots. Capillary closure, retinal microaneurysms and neovascularization following massive fundus hemorrhage could be involved in few of the above instances. However, single choroidal neovascularization (CNV) in macular has not been observed in acute myelocytic leukemia (AML). Patient concerns: A 22-year-old woman presented with a 7-day history of vision decline in the right eye (OD). The patient was diagnosed as M3 AML one month earlier. Chemotherapy was immediately administered, which led to temporary myelosuppression. Recent examination showed that best corrected visual acuity was 20/400 OD. Fundoscopy showed petechial and patchy intra-retinal hemorrhage in both eyes and grayish-white lesion in the right macular center, which was confirmed as macular CNV by OCT and OCTA. Diagnoses: The patient was diagnosed as macular CNV OD related to AML and chemotherapeutic regimens. Interventions: She received intravitreal ranibizumab injection 0.5 mg (10 mg/ml) in the right eye for once on January 3, 2017. Outcomes: CNV resolved three days after treatment with intravitreal ranibizumab injection 0.5 mg for once. No recurrence was observed after 10-month follow-up. Vision recovered to 20/40 at the last visit. Lessons: This is the first report demonstrating that macular CNV could be an ophthalmic side-effect secondary to initiated chemotherapeutic regimens in patients with M3 AML. Intravitreal injection of ranibizumab could be beneficial and safe in treating this CNV.